Evolving Concepts in Insulin Resistance - Infante, Marco (IntechOpen, 2022)
Over the last decades, the growing prevalence of insulin resistance has dramatically contributed to the global epidemic of metabolic syndrome, obesity, type 2 diabetes mellitus, and cardiovascular disease. Therefore, there is an unmet need for novel nutritional and pharmacological strategies aimed to prevent or treat insulin resistance and its related comorbidities. This book presents a comprehensive overview of the pathophysiology and clinical consequences of insulin resistance in different settings, describing novel diagnostic biomarkers and molecular targets of this condition.